Does Reoperation Risk Vary for Different Types of Pediatric Scoliosis?. Issue 9 (October 2018) - Paul, Justin C.; Lonner, Baron S.; Vira, Shaleen; Feldman, David; Errico, Thomas J.
Abstract : Study Design: Retrospective cohort study of spine fusion surgery utilizing the New York State Inpatient Database. Objective: The objective was to determine whether there were differences in reoperation rates among pediatric scoliosis associated with various etiologies compared with idiopathic scoliosis. Summary of Background Data: The incidence of postoperative complications and reoperations is known to vary among patients with diverse scoliosis pathologies. As these are heterogeneous conditions and often with rare occurrence, it is difficult to compare them in a single study. We aimed to assess reoperation events after fusion for several etiologies of pediatric scoliosis. Methods: The 2008 to 2011 New York State Inpatient Database was queried using International Classification of Diseases (ICD-9-CM) codes for patients with in-hospital stays including a spine arthrodesis for scoliosis. All approaches, all fusion lengths, and ages 10 to 21 were included. Patient identifiers and linkage variables were used to identify revisits. The relative risk of reoperation was calculated for several rare conditions associated with scoliosis. Results: Two thousand three hundred fifty-six pediatric scoliosis fusion surgeries were identified in 2008 in the state of New York. The 1- and 4-year reoperation rate for idiopathic scoliosis was 0.9% and 1.6%, respectively. For nonidiopathic scoliosis, the 1- and 4-year rates were 4.2% and 20.4%, respectively. Of the nonidiopathic scoliosis subtypes, congenital scoliosis (4.7% risk at 1 y, 41.6% at 4 y), the neuromuscular disease arthrogryposis (7.3% risk at 1 y, 28.6% at 4 y), and syndrome neurofibromatosis (9.1% at 1 y, 32.3% at 4 y) showed the highest risk for reoperation. Length of stay and hospital charges were higher for reoperations. Conclusions: Using a large administrative database, we identified neuromuscular, syndromic, and congenital forms of scoliosis that have the highest relative risk for a reoperation within 1 year. At-risk populations should be identified and resources allocated and preventative measures instituted accordingly to prevent these costly events. Level of Evidence: Level III.